2011
DOI: 10.1007/s00330-011-2174-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of diffusion-weighted magnetic resonance imaging in bladder cancer: potential utility of apparent diffusion coefficient values as a biomarker to predict clinical aggressiveness

Abstract: DW-MRI exhibits high diagnostic performance in bladder cancer with excellent objectivity. The ADC value could potentially serve as a biomarker to predict clinical aggressiveness in bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 31 publications
(48 reference statements)
10
109
1
6
Order By: Relevance
“…In the various studies, different approaches were used; most of them used both T2W and DWI [8] [10] [15], but some evaluated the sequences separately in identifying the tumor [7] [15]. The sensitivities and specificities in the present study are lower than those studies.…”
Section: Discussionmentioning
confidence: 75%
“…In the various studies, different approaches were used; most of them used both T2W and DWI [8] [10] [15], but some evaluated the sequences separately in identifying the tumor [7] [15]. The sensitivities and specificities in the present study are lower than those studies.…”
Section: Discussionmentioning
confidence: 75%
“…The inconsistency may due to the fact that there is substantial interviewer variation of the ADC value for any particular region of interest in a relatively thin bladder wall [39]; moreover, the ADC value may be difficult to reproduce since it can alter between systems depending on many variables including the coil system, the vendor, the imaging protocol and others. It may be affected by many factors associated with variability in the subject's tissue itself, and this would include such variables as body temperature, tissue pressure, perfusion rate or the magnetic environment of each individual, and so on [40,41].…”
Section: Initial Results For Bladder Tumor Stagingmentioning
confidence: 99%
“…In fact, Kobayashi's group reported the histopathological diagnosis of 6 tumors with the "inchworm sign" on DWI as muscle-invasive bladder cancer. 7 Although bladder tumors with stalks on MR imaging tend to be of low stages, thickness of the bladder wall at the base of the stalk should be evaluated carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that MR imaging at 1.5T facilitates the detection of stalks and staging of bladder tumors. 5,7,10 However, we believe no study has compared MR imaging sequences with regard to the efficacy of stalk detection.…”
Section: Introductionmentioning
confidence: 99%